1992
DOI: 10.2105/ajph.82.4.528
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with AIDS risk behaviors among high school students in an AIDS epicenter.

Abstract: BACKGROUND. A greater understanding of the determinants of risky behaviors is an essential precursor to the development of successful AIDS prevention programs for adolescents. METHODS. A survey measuring AIDS-related behaviors, beliefs, and knowledge was administered to a sample of 531 10th-grade students residing in an AIDS epicenter. RESULTS. Of the 56.8% of students reporting past-year involvement in sexual intercourse, 67.3% reported unprotected intercourse with low-risk partners, 1.3% reported unprotected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 21 publications
1
47
0
1
Order By: Relevance
“…Individuals aremorelikely to engage in AIDS riskbehaviors if theyperceive that their peers are engaging in this type of behavior (Auerbach & Coates, 2000;DiClemente, 1991;Walter et al,1992). The health practitioner can help individuals determine whatpeers in the social network feel aboutthelatestHIVtreatments, aswell astheirlevel of riskbehavior.…”
Section: Promoting Prevention In the Era Of New Treatmentsmentioning
confidence: 99%
“…Individuals aremorelikely to engage in AIDS riskbehaviors if theyperceive that their peers are engaging in this type of behavior (Auerbach & Coates, 2000;DiClemente, 1991;Walter et al,1992). The health practitioner can help individuals determine whatpeers in the social network feel aboutthelatestHIVtreatments, aswell astheirlevel of riskbehavior.…”
Section: Promoting Prevention In the Era Of New Treatmentsmentioning
confidence: 99%
“…They found that both men and women perceived their best friend's oral sex behavior to be similar to their own but found no relationship with sexual intercourse. Prior research on the referent self in comparison with perceptions of close friends has been explored in areas such as health and social status [52] and AIDS risk behaviors [50]. These studies demonstrated that participants differentiated between their close friends and the typical person, believing that their close friends were more similar to themselves than the average person.…”
Section: Introductionmentioning
confidence: 99%
“…For example, adolescent cigarette, alcohol, and marijuana use is related to that of friends and potential friends (Aloise-Young, Graham, & Hansen, 1994;Dembo, Farrow, Schmeidler, & Burgos, 1979;Hartford, 1985;Urberg, Degirmencioglu, & Pilgrim, 1997). Similarly, researchers have found that youths' sexual behaviors are linked to the norms and behaviors of their peers and friends (Dolcini & Adler, 1994;Morrison, Baker, & Gillmore, 1998;Prinstein, Meade, & Cohen, 2003;Walter et al, 1992), and that youth tend to be similar to their friends with respect to sexual behaviors, expectations, and feelings (Billy, Rodgers, & Udry, 1984).…”
mentioning
confidence: 99%